Bannlosung (nam-erim-bur-ru-da) : die therapie eines auf eidliche falschaussage zuruckgefuhrten leidens. (Wissenschaftliche Veröffentlichung der Deutschen Orient-Gesellschaft., 2019)
In volume 10 of the cuneiform texts from Assur literary content (KAL), a hitherto completely unknown text corpus is presented in two sub-volumes. The cuneiform manuscripts, assembled from many small fragments, document a therapeutic procedure that was called "bane release" (Sumerian: nam-érim-búr-ru-da) in the ancient Near East. The aim of the therapy was to free the symptoms and causes of a severe māmītu ailment (accad.: "Bann"), the origin of which was located in the guilt of a false statement on oath. The writings of the healers provide information about the complex measures for the treatment of the 'ban-suffering' and put our understanding of the ancient oriental conceptions of illness and healing on a new basis. The 81 texts assigned to the corpus were written between the late 2nd millennium and the 6th century BC. recorded on clay tablets. The vast majority are from Assyria. The remainder came to light at other sites in Assyria, and a few also in Babylonia. The first volume contains a detailed introduction and a catalog that provides information about the form and content of the individual texts. The philological edition that forms the main part provides transliteration, translation and commentary on the medicinal cuneiform texts. The second volume contains several indexes, including glossaries and subject indices, as well as illustrations of the cuneiform texts in the form of hand drawings and photographs.